THE EFFECT OF CONSUME GINGER AND HONEY BISCUITS ON THE FRECUENCY OF NAUSEA AND VOMITING IN TEENAGE PREGNANCY - Citra Indah Fitriwati; Setyowati Setyowati; Tri Budiati (Journal of Maternity Care and Reproductive Health, 2019)
The risk of complication that occur during pregnancy at a young age increasing maternal and infant mortality. Nausea and vomiting occur commonly during pregnancy but it will risk becoming more severe in teenage pregnancy, so it need to be prevented. Nonpharmacological therapy with ginger honey biscuits was used in this quantitative study to relieve nausea and vomiting in teenage pregnancy. Quasi-experiment design was used in this study with pre and post test of 32 respondents in control group and 32 respondents in intervention group. The respondent is teenage pregnancy 12-19 years old and experience nausea, vomiting. Pregnancy Unique Quantification of Emesis and Nausea (PUQE) Questionnaire used in this study to show the nausea and vomiting scores experienced by teenage pregnancy pre and post intervention ginger honey biscuits. This study conducted to identify the effect of consuming ginger biscuits and honey on the frequency of nausea and vomiting in teenage pregnancy. The results showed that there was a difference in the frequency of nausea and vomiting of teenage pregnancy before and after consume ginger honey biscuits. The recommendation of this research is the using of ginger honey biscuits as nursing intervention to relieve nausea and vomiting in teenage pregnancy.Keywords: ginger honey biscuits; nausea and vomiting; teenage pregnancy.